2021
DOI: 10.2147/ott.s291267
|View full text |Cite
|
Sign up to set email alerts
|

Targeting c-MET to Enhance the Efficacy of Olaparib in Prostate Cancer

Abstract: Prostate cancer is the second leading cause of cancer death in men worldwide. Olaparib is clinically approved for the treatment prostate cancer, but cytotoxicity and offtarget effects including DNA damage limit its clinical applications. In the current study, new strategies to improve the therapeutic efficacy of olaparib for the treatment of prostate cancer were investigated. Methods: Two prostate cancer cell lines were exposed to the c-MET inhibitor PHA665752 and/or the PARP inhibitor olaparib. Cell counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…At present, olaparib has been clinically approved for the treatment of PCa, but cytotoxicity and DNA damage limit its clinical application. Z. Wang et al (58) found that the combined inhibition of c-Met and poly ADP-ribose polymerase(PARP) had a synergistic effect on blocking the growth of PCa cell lines. When the two drugs were combined, tumor invasion and migration were prominently inhibited.…”
Section: Clinical Studies Of C-met Targeting Therapy In Urologic Neop...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, olaparib has been clinically approved for the treatment of PCa, but cytotoxicity and DNA damage limit its clinical application. Z. Wang et al (58) found that the combined inhibition of c-Met and poly ADP-ribose polymerase(PARP) had a synergistic effect on blocking the growth of PCa cell lines. When the two drugs were combined, tumor invasion and migration were prominently inhibited.…”
Section: Clinical Studies Of C-met Targeting Therapy In Urologic Neop...mentioning
confidence: 99%
“…Z. Wang et al. ( 58 ) found that the combined inhibition of c-Met and poly ADP-ribose polymerase(PARP) had a synergistic effect on blocking the growth of PCa cell lines. When the two drugs were combined, tumor invasion and migration were prominently inhibited.…”
Section: Clinical Studies Of C-met Targeting Therapy In Urologic Neop...mentioning
confidence: 99%
“…It has been reported that c-Met targeting can be used in the treatment of NSCLC, prostate cancer, gastric cancer, and other tumors [ 40 , 41 , 42 , 43 ]. New triazolo-pyridazine/pyrimidine derivatives were synthesized, evaluated, and found to inhibit c-Met kinase in A549, MCF-7, and HeLa cell lines that overexpressed c-Met.…”
Section: New Potential Heterocyclic Molecular Targeted Drugsmentioning
confidence: 99%
“…A variety of drugs are currently being used to study whether they can enhance the efficacy of olaparib in cancer treatment. Studies have shown that abiraterone, foretinib, PHA6657, and other drugs in combination with olaparib have synergistic effects when they act on tumor cells [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%